2015
DOI: 10.1007/s00122-014-2449-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and genetic mapping of the putative Thinopyrum intermedium-derived dominant powdery mildew resistance gene PmL962 on wheat chromosome arm 2BS

Abstract: Powdery resistance putatively derived from Thinopyrum intermedium in the wheat line L962 is controlled by a single dominant gene designated PmL962 and mapped to chromosome arm 2BS. Powdery mildew, caused by Blumeria graminis f. sp. tritici (Bgt), is a destructive disease affecting the production of wheat (Triticum aestivum). Powdery mildew resistance was putatively transferred from Thinopyrum intermedium to the common wheat line L962, which conferred resistance to multiple Chinese Bgt isolates. Genetic analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Twentyseven Blumeria framinis f.sp. tritici (Bgt) single-spore isolates (Shen et al 2015) were collected from Beijing, Shandong, Hebei, Henan, and Jiangsu provinces to assess the reactions of all genotypes to the pathogen causing powdery mildew. Evaluation of seedling reactions to 27 isolates was conducted in a greenhouse using the previously reported method (Zhao et al 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twentyseven Blumeria framinis f.sp. tritici (Bgt) single-spore isolates (Shen et al 2015) were collected from Beijing, Shandong, Hebei, Henan, and Jiangsu provinces to assess the reactions of all genotypes to the pathogen causing powdery mildew. Evaluation of seedling reactions to 27 isolates was conducted in a greenhouse using the previously reported method (Zhao et al 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the three genotypes exhibited positive agronomic traits such as PH (70~75 cm) and TGW (Table 2). In addition, L962 was found to be resistant to powdery mildew (Shen et al 2015) (Figure 1C) while both L958 and L987 were susceptible to powdery mildew. Regarding the stripe rust resistance, the specific PCR amplification result indicated that L958 and L987 carry the WCBP1 gene ( Figure 1D) for resistance to stripe rust.…”
mentioning
confidence: 99%
“…In China, powdery mildew is increasing its importance and for the last decade more than six million hectares of wheat cultivated area have been affected annually. Currently it is more dangerous than any other wheat diseases for this region (Zeng et al, 2014;Ma et al, 2015;Shen et al, 2015;Mwale et al, 2017). Some researchers predict powdery mildew to become more important in the future because of the climate change, which will provide more favourable conditions for the development of the disease (Tang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Wheat powdery mildew is caused by the fungus Blumeria graminis and is one of the most common diseases that result in significant loss of crop yield and quality in China [1][2][3]. Recently, wheat powdery problems [27].…”
Section: Introductionmentioning
confidence: 99%